2016
DOI: 10.1007/s40262-016-0393-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Food and Pharmaceutical Formulation on Desmopressin Pharmacokinetics in Children

Abstract: Introduction: Desmopressin is used for nocturnal enuresis treatment in children. In this study, we investigated the pharmacokinetics of two formulations: a tablet and a lyophilisate, in both fasted and fed children.Methods: Previously published data from two studies (22 children aged 6 to 16 yr and 25 children aged 6 to 13 yr) were analyzed using population pharmacokinetic modeling. A 1-compartment model with first order absorption was fitted to the data. Covariates were selected using a forward selection proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…The SAFE-PEDRUG project explored the value of the porcine juvenile animal model3 and PK modelling4 (population pharmacokinetics and physiological-ly based pharmacokinetic modelling) in providing prior paediatric PK/PD knowledge, before the actual adult trials have been completed. For the evaluation of this approach, three case compounds were selected: des-mopressin, lisinopril, and fluoroquinolones.…”
Section: Resultsmentioning
confidence: 99%
“…The SAFE-PEDRUG project explored the value of the porcine juvenile animal model3 and PK modelling4 (population pharmacokinetics and physiological-ly based pharmacokinetic modelling) in providing prior paediatric PK/PD knowledge, before the actual adult trials have been completed. For the evaluation of this approach, three case compounds were selected: des-mopressin, lisinopril, and fluoroquinolones.…”
Section: Resultsmentioning
confidence: 99%
“…Most articles describing the PK parameters of desmopressin administered to adults (Fjellestad-Paulsen et al, 1993 ; Agersø et al, 2004 ; Fransén et al, 2009 ) applied a two- or three-compartmental model to fit the data. Michelet et al ( 2016 ) combined the data collected in children by Osterberg et al ( 2006 ) and De Bruyne et al ( 2014 ) and concluded that a one-compartmental model with first-order absorption best described the data. In the current study, a two-compartmental model was chosen based on a smaller OFV (ΔOFV = 87.42) in comparison with a one-compartmental model, despite the high values of RSE and shrinkage for V 2 /F (31.4 and 61.8%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma concentrations below the LOQ were excluded from the analysis (4 pg/mL; n = 8%) and a logarithmic transformation of the remaining plasma concentrations was performed. A one-compartmental model with first-order absorption was chosen as the pop-PK base model, analogous to the human pop-PK model development (Michelet et al, 2016 ). Subsequently, based on a visual exploration of the plasma concentration-time profiles obtained in the growing piglets, a two-compartmental disposition model and a dual-input were evaluated to describe the absorption of the sublingual desmopressin lyophilisate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiologically based pharmacokinetic (PBPK) modelling is used to predict food effects although it is acknowledged that these models are much more predictive of adult populations compared to children [8]. Preclinical development efforts for drug development are likely to include in vitro screening of transporter substrate activity and metabolic profiling to identify potential food effects as part of the standard development pathway.…”
Section: Introductionmentioning
confidence: 99%